2009
DOI: 10.3390/ijerph6061812
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Smoking Habit among Greek Blue and White Collar Workers

Abstract: The aim of our study was to investigate the prevalence of smoking in a Greek working population. A questionnaire regarding smoking habit was collected from 1,005 out of 1,200 blue and white-collar employees (response rate: 84%). The overall smoking prevalence was 48.4% and did not differ by sex, age, education, and occupation. The mean cigarette consumption per day was 25.54, with no difference observed by occupation. The above-mentioned findings, if confirmed by further research, are alarming and inconsistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
7
1
10
Order By: Relevance
“…The tobacco prevalence was lesser than those reported by Nagao et al [10] among industrial workers in Japan's overseas enterprises in the United Kingdom, Rachiotis et al [11] among Greek blue and white collar workers (48.4%).…”
Section: Discussioncontrasting
confidence: 53%
“…The tobacco prevalence was lesser than those reported by Nagao et al [10] among industrial workers in Japan's overseas enterprises in the United Kingdom, Rachiotis et al [11] among Greek blue and white collar workers (48.4%).…”
Section: Discussioncontrasting
confidence: 53%
“…This finding was in line with previous studies, which reported a high prevalence of smoking among Greek industrial workers. 27,28 Our findings on smoking could form the base for the development of workplace-based anti-smoking activities. It has been suggested that an effective anti-smoking policy in worksite should not be isolated, but integrated into a broader context of occupational health and safety and health promotion.…”
Section: R T I C L E a R T I C L Ementioning
confidence: 84%
“…Such a holistic approach could significantly reduce both occupational exposures and prevalence of smoking among industrial workers. 27 Cotton ginning was the cotton industry sector with the highest burden of respiratory illnesses compared to spinning, weav-…”
Section: R T I C L E a R T I C L Ementioning
confidence: 99%
“…One possible reason for the high smoking rates among blue collar workers is that blue collar workers such as Operating Engineers are often outdoor workers and hence, do not benefit as much from anti-smoking policies, which have been found to be among the most effective smoking cessation interventions in the general population (Rachiotis, Karydis, Drivas, & Hadjichristodoulou, 2009). In general, public health efforts have led to a reduction in smoking prevalence among white collar workers, but have had little impact among blue collar workers.…”
Section: Introductionmentioning
confidence: 99%